Modeling Human Femoral Neck Using a 2D Structure. (2015) - Botean, Adrian-Ioan; Mândru, Dan; Hărdău, Mihail
Abstract: This paper analysis the macro-scale structure of the human proximal femoral bone, proposing a 2D model that allows the study of stresses and strains, especially in the femoral neck and not only. Is presented here a numerical analysis of the behavior under mechanical load of the cortical and cancellous (spongy) bone. In the end of this paper is shown a 2D model, made of epoxy resin, which can be used to study the state of stresses and strains in the femoral bone that shows the osteoporosis, fractures, implants, prosthetics.Selection and/or peer-review under responsibility of "PetruMaior" University of TirguMures, Faculty of Engineering.